University students' nomophobia prevalence, sociodemographic factors and relationship with academic performance at a University in Oman. (2020) - Qutishat, Mohammed; Rathinasamy Lazarus, Eilean; Razmy, A Mohamed; Packianathan, Samson
Abstract: Background: Nomophobia "no mobile phone" and phobia" is a pathological fear of being out of contact with a mobile phone, has no mobile networks, or has insufficient balance or battery. Purpose of the study: To determine the prevalence of nomophobia, demographic factors affecting nomophobic behaviors, and the relationship between nomophobia and academic performance among university students in Oman. Methods: A descriptive correlational study design was chosen to describe the prevalence of nomophobia among Sultan Qaboos University students. A convenience sampling technique was used to select 735 students based on defined inclusion criteria. Nomophobia was identified using a self-report instrument, the Nomophobia Questionnaire, which includes 20 Likert scale items rated from 1 ("strongly disagree") to 7 ("strongly agree"). Descriptive analysis and a Pearson correlation statistical test were used to determine the possible relationship between nomophobia and academic performance. Results: The prevalence of nomophobia among students was 99.33%, most with a moderate level of nomophobia. Students with severe nomophobia reported weak academic performance ( p = .706), but this was not statistically significant. Conclusion: This study found a high prevalence of nomophobia and a weak relationship with academic performance. More studies should be conducted in this area to inform policy on cellphones within academic premises, to avoid serious ill effects of chronic use.